Why Leaders Fail Ethically: A Paradigmatic Evaluation of Leadership - Batmanghlich, Cameron A (Springer, 2015)
Contrary to popular conceptions that ethical failures in leadership are correlated with economic downturns and other stressful market conditions, this book argues that such transgressions are an intrinsic element of leadership, as it is defined under the current prevailing paradigm.